Literasi Teologi Digital: Menjawab Tantangan Disrupsi dalam Pendidikan Kristen Kontemporer - Situmorang, Anen Mangapul; Halawa, Iman Kristina (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2024)
The digital revolution has triggered disruption in various fields, including in the education system and religious practices. Contemporary Christian education is faced with the challenge of adapting to the rapid development of information technology without losing the essence of faith values. This research aims to explore the concept of digital theological literacy as a strategic approach in responding to the disruption challenge. Using a literature study method and a theological-contextual approach, this article analyses the urgency of developing digital competencies based on Christian values, both among educators and students. The results of the study show that digital theological literacy includes not only technical skills, but also critical abilities in understanding, filtering, and reflecting on digital information based on theological principles. This literacy plays an important role in forming a solid faith identity, encouraging learning transformation, and maintaining spiritual integrity in the midst of digital globalisation. Therefore, the integration of digital theological literacy in the Christian education curriculum is needed as a form of strategic and prophetic response to the era of disruption.